Examples of Huzur-i Humayun Lessons in the Ottoman, Critical Edition of Commentary Text with Dissection and Criticizing III - TEMİZER, AYDIN (ATATURK UNIV, FAC THEOLOGY, 2018)
The lessons, which were performed in Ramadan in the presence of the Ottoman sultans on the exegesis of the Quran, were called Huzur-i Humayun Lessons. One of the good examples of these lessons was the commentary on the 50th and 51th verses of Surah al-Araf, which was presented by al-Hajj Umar Lutfi Efendi in the presence of the Sultan Abdul-Hamid, the Second, in the month of Ramadan in 1295 AH. After the presentation, thirty questions were directed to Umar Lutfi Efendi, and nearly all of these questions were related to the nature of language of Qur'an. In this article, tafseer lesson which took the 50th and the 51st verses of Surah al-Araf as subject edited critically with its presentation and discussion chapters. First chapter of this lesson that has been named takrir (presentation) is in Ottoman Turkish. This part was written by the Latin alphabet. Second chapter of this lesson that has been named munazara (discussion) is in Arabic. This part was written by translating into Turkish. On the other hand, some sample photos from original manuscripts were added to the article. The text published in this study was written on the basis of the manucript's copy from the Topkapi Palace Museum.
Keywords: Qur'an; Tafseer; Ottoman; Huzur-i Humayun Lesson; Ramadan; Presentation; Discussion